Neurosyphilis in HIV-infected patients - T. V. Krasnoselskikh; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
A review article is addressed the issue of the diagnosis and treatment of neurosyphilis that is developing against the background of HIV-infection. HIV-infected patients are at higher risk of neurologic, ocular and auricular manifestation of syphilis as well as treatment failures and relapses. Diagnosis of neurosyphilis in HIV-positive patients is complicated because both infections cause similar changes in the cerebrospinal fluid (CSF). The effectiveness of neurosyphilis treatment in patients with HIV co-infection is difficult to estimate, since the normalization of their CSF goes slower comparing to HIV-negatives. The increase in incidence of syphilis and HIV co-infection is anticipated in the coming years. This necessitates a comprehensive study of the problem and requires the development of new approaches to neurosyphilis diagnosis and treatment in co-infected patients.